Tales of the Fish Patrol - London, Jack, 1876-1916 (Salt Lake City, UT : Project Gutenberg, 1997)
"Tales of the Fish Patrol" by Jack London is a collection of engaging stories written during the early 20th century. The book centers around the adventures and challenges faced by fish patrolmen tasked with enforcing the regulations on fishing in and around San Francisco Bay. It introduces a cast of colorful characters, including the young narrator who becomes a deputy patrolman, and dives into the conflicts between the patrolmen and various fishermen, particularly focusing on the Chinese shrimp-catchers and Greek fishermen. The opening of the book sets the stage for a thrilling account of the narrator's experiences as a deputy patrolman during a raid on Chinese shrimp-catchers operating illegally. As a young and eager sailor aboard the sloop "Reindeer", he describes the excitement and tension of the operation, which includes capturing illegal fishing vessels and dealing with the fierce reactions of the fishermen. The narrative captures both the struggles of enforcing fish laws against defiant fisherman and the interpersonal dynamics among the patrolmen, ultimately immersing the reader in the lively drama of life on the bay. (This is an automatically generated summary.)
White and yellow -- The King of the Greeks -- A raid on the oyster pirates -- The siege of the "Lancashire Queen" -- Charley's coup -- Demetrios Contos -- Yellow handkerchief.
There is an improved edition of this title, eBook #28693
Release date is 1997-05-01
Transcribed from the 1914 William Heinemann edition by David Price
Keywords: Short stories; Immigrants -- Fiction; Fishers -- Fiction; Fishing villages -- Fiction; San Francisco Bay Area (Calif.) -- Fiction